Wrapping tape operation (wto) for poststenotic aneurysm of ascending aorta during correction of aortic stenoses - Popov, V. V.; Bolshak, O. O.; Lazorishinetz, V. V. (Ukrainian Journal of Cardiovascular Surgery, 2016)
To determine possibilities of correction of poststenotic aneurysm of ascending aorta (PAAA) by WTO. During 2005–2015. 141 patients (pts) with aortic stenoses (AS) and PAAA were operated in Institute. The following operation was performed: aortic valve replacement (AVR) + wrapping tape operation (WTO) of AA. In all cases after AVR nylon tape (diameter 1 cm) was wrapping of AA by 5–9 tours and fixation between them and in proximal and distal part of AA. Hospital mortality was 0,6%. Echo examination of diameter of AA (mm): preoperative 48,5±1,6, postoperative 40,4±1,3, remote period 41,2±1,8. On the basis of clinical experience we recommend the expedient method of WTO for PAAA (diameter of AA till 5,5 cm) during AVR without prostheses of AA.